Temperature Field Analysis for Engagement Process of Friction Disc in Wet Clutch - Yang Yongqiang; Wang Zhongmin; Wang Yongqin (Jixie chuandong)
The dynamics model of friction clutch of a mine locomotive is established, and the angular speed and heat flux of the master-slave friction disc in engagement process are solved by Euler method. The radial heat conduction equation of engagement process of friction disc in wet clutch is established, and the differential quadrature method is used to discretize the heat conduction equation and boundary conditions. The Runge-Kutta method is used to calculate the temperature rise of friction disc changing with time and radius under nominal and full-load conditions of mining locomotive. The results show that the radial varying temperature of the friction disc increases with the increase of time and radius during the engagement process. The greater the load, the longer engagement time and higher corresponding temperature. This conclusion provides a theoretical basis for the design and performance analysis of friction clutch.